Development Of Learning Media Based On Wondershare Filmora Software On Integrated Thematic Learning Elementary School - M Aidhal Fikri; Yanti Fitria (ILIN Institute, 2022)
This study aims to determine the validity and practicality of learning media based Wondershare Filmora software  in integrated thematic learning. This type of research is R&D (Research and Development). This means that research is responsible for the results of new products or improvements to existing products. This study uses a 4-D development model. Consists of define, design, development, and disseminate. The subjects of the pilot study were 3 experts, 1 class teacher and 30 third grade elementary school students. The instruments used were expert validation sheets, teacher and student response questionnaires. The results showed: (1) Wondershare Filmora software  in integrated thematic learning theme 6 Energy and its Changes in Elementary School was declared very valid with an average score of 94,12% media experts, material experts 90.67% and linguists 97.50%, (2) Teacher and student responses to software -based learning media trials Wondershare Filmora in Elementary School obtained a very practical category with an average value of 92.50% teacher responses and 95.83% student responses.